Impact of different pectin levels and banana varieties on the nutritional and sensory properties of banana jam - Shakir, Mohammad; Pahnwar, Aasia Akbar; Irshad, Asif; Sheikh, Saghir Ahmed; Meghwar, Parkash; Khan, Alam; Ghafoor, Imtiaz; Ali, Ayaz (Journal of Pure and Applied Agriculture, 2024)
Banana is a significant crop worldwide, and it is prone to spoilage after ripening. Processing bananas into food products reduces their post-harvest losses and promotes food security. Jam is a popular banana product, and its preparation is influenced by several factors, including pectin content and different banana varieties. The current research aimed to assess the nutritional and sensory properties of banana jam developed from Cavendish dwarf (local variety) and Indial long (hybrid variety) and treated with three different levels of pectin i.e., 5, 10, and 15 g kg-1. The results revealed that 15 g kg-1 pectin levels resulted in a better nutritional profile and sensory attributes, with 0.72% ash, 61.59% TSS, 4.28 pH, 13.84 mg 100 g-1 vitamin C, 4.34% protein, 40.10% carbohydrate, 1.34% fat, 0.50% crude fiber, 0.32% titratable acidity, 78.13 mg 100 g-1 potassium, 0.82 mg 100 g-1 iron, 1.56 mg 100 g-1 calcium, 1.36 mg 100 g-1 magnesium, 29.62 mg 100 g-1 sodium, and sensory scores of 7.87 for color, 7.78 for flavor, 7.85 for texture, and 7.92 for overall acceptability. This was followed by the 10 g and 5 g kg-1 pectin levels. Similarly, the results of varieties showed the Indial long variety to have superior nutritional and sensory qualities compared to the Cavendish dwarf variety, with 0.86% ash, 54.20% TSS, 4.23 pH, 12.78 mg 100 g-1 vitamin C, 4.56% protein, 39.29% carbohydrate, 1.15% fat, 0.37% crude fiber, 0.33% titratable acidity, 78.01 mg 100 g-1 potassium, 0.81 mg 100 g-1 iron, 1.62 mg 100 g-1 calcium, 1.27 mg 100 g-1 magnesium, and 29.67 mg 100 g-1 sodium. Its sensory scores were 7.93 for color, 7.83 for flavor, 7.90 for texture, and 7.96 for overall acceptability. It can be concluded that banana jam prepared with a pectin ratio of 15 g kg-1 has better nutritional and sensory characteristics. The results reflected that the Indial long variety was more suitable for banana jam production as compared to the Cavendish dwarf variety.